Direitos humanos no século XXI: a redução da pobreza e a proteção dos direitos sociais na Constituição Federal de 1988 - Pereira, Milena Carla Azzolini (2010)
Despite all legal protection of the human rigths, they are often violated. This work intends to evaluate the reasons why poverty and its results can be consider the causes of this rights violation. Once the protection assured by formal equality showed itself insufficient, the ideal of real equality started to be reached. Because of this, economics and social measures are required to struggle the poverty. In this view, social rights, realized by the state, are an important way to give social welfare to people and provide real perspective to change this reality